Relationships between fish stock changes in the Baltic Sea and the M74 syndrome, a reproductive disorder of Atlantic salmon (Salmo salar) - Mikkonen, Jaakko; Keinänen, Marja; Casini, Michèle; Pönni, Jukka; Vuorinen, Pekka J. (ICES Journal of Marine Science, 2011)
<qd> Mikkonen, J., Keinänen, M., Casini, M., Pönni, J., and Vuorinen, P. J. 2011. Relationships between fish stock changes in the Baltic Sea and the M74 syndrome, a reproductive disorder of Atlantic salmon ( Salmo salar ). – ICES Journal of Marine Science, 68: 2134–2144. </qd>The M74 syndrome of Baltic salmon ( Salmo salar ), which appears as increased yolk-sac fry mortality (YSFM), impairs the reproduction of salmon stocks. Changes in the prey stocks of Baltic salmon in its two feeding areas, the southern Baltic Proper (BPr), where sprat ( Sprattus sprattus ) was the main prey species during the high incidence of M74, and the Bothnian Sea, where herring ( Clupea harengus ) is the dominant species, were analysed in relation to salmon growth and size and in relation to the incidence of M74. The high condition factor (CF > 1.05) of prespawning salmon predicted high YSFM. From the various stock factors of sprat and herring in the southern BPr, the biomass of sprat had the strongest positive relationships with the CF of prespawning salmon, and the total prey biomass with YSFM. It is concluded that the ample but unbalanced food resources for salmon in the BPr, primarily sprat, induce M74. By reducing the fishing pressure on cod ( Gadus morhua ) and by more effectively managing the sprat fishery in years when the cod stock is weak, the incidence of the M74 syndrome could be reduced and even prevented.